Using finite elements in mechanical design - Mottram, James Toby.; Shaw, Christopher T. (Christopher Thomas). (London : McGraw-Hill, 1996)
This book is about: Relationship between design and finite elements; Structural mechanics; Finite element solutions of the equations; Implementing a computer-based analysis procedure; Building the geometry description and the mesh; Obtaining and analysing the results; ..
Includes index.
Keywords: Data processing; Engineering design; Finite element method; Computer-aided design; Finite element method -- Data processing; Machine design -- Data processing; Engineering -- Data processing